Installation errors in calculating large-panel buildings (rus) - Nedviga E.S.; Kuznetsov V.D.; Vatin N.I. (Инженерно-строительный журнал, 2011)
Every year the problem of civil and erection work quality gets sharper in Russia. The article is devoted to solving the identified problem not from the point of organizational and technological aspects of building but from the point of design and calculation. The paper considers the influence of offsetting and axes fractures of wall panels in the process of its installation into large-panel building. Comparative analysis of design schemes that takes into account different types of errors in installation is done. The structure calculation taking into account errors of details installation was made. Obtained efforts in structural elements exceeded allowable values prescribed in the standard documentation. Conclusions about need to consider installation errors (caused by a deviation from the design of vertical structures) in design model were made, including calculation in the CAD software.